Triage Knowledge of Emergency Rooms Nurses at Dr Soetomo Regional General Hospital - Fariza Nur Aini Widyani; April Poerwanto Basuki; Djohar Nuswantoro (Indonesian Journal of Anesthesiology and Reanimation, 2020)
Introduction: Triage is a system to sort patients based on their urgency for care during an emergency. In addition, to determine patient's severity, triage reduces time wasted and overcrowding in the emergency room.1 Triage errors such as over-triage or under-triage must not exceed 35% and 5% of the total numbers of patients respectively. Dr. Soetomo General Hospital of Surabaya with its status as one of type "A” hospital in Indonesia that has good amenities, facilities, and infrastructures which is also the main referral hospital from Primary or Secondary Health Care, is prone to patients overcrowding. The high number of patients and the demands for high-quality service as the main referral hospital require higher qualification from health care professionals in term of cognitive, skills, and attitude. Objective: This study conducted to evaluate the level of knowledge of the ER (Emergency Room) nurses at Dr. Soetomo General Hospital in 2019 towards triage. Methods and Materials: This study is a quantitative descriptive study using a validated questionnaire with 32 nurses as the samples. Results and Discussion: Demographic profile showed that majority of nurses are: female (52%), age 26 – 35 years old (46 %), graduated from D3 (61%), have been working in this field for >15 years (46%), attended Basic Life Support Training (33%), and have moderate knowledge in triage (61%). Conclusion: Emergency room nurses of Dr Soetomo General Hospital had adequate knowledge in triage. The researcher considers there might be some factors influencing nurse's knowledge in triage.